2011
DOI: 10.1098/rspb.2011.0168
|View full text |Cite
|
Sign up to set email alerts
|

Leadership in elephants: the adaptive value of age

Abstract: The value of age is well recognized in human societies, where older individuals often emerge as leaders in tasks requiring specialized knowledge, but what part do such individuals play in other social species? Despite growing interest in how effective leadership might be achieved in animal social systems, the specific role that older leaders may play in decision-making has rarely been experimentally investigated. Here, we use a novel playback paradigm to demonstrate that in African elephants ( Loxo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
200
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(215 citation statements)
references
References 40 publications
(70 reference statements)
6
200
1
Order By: Relevance
“…McComb et al (10) provide suggestive data that the age of the herd's matriarch affects their response to Maasai boys, with older matriarchs less likely to retreat from their voices than younger matriarchs. In another study, herds led by older matriarchs reacted more appropriately to threats from male lions than those led by younger, less experienced females (12). Typical responses to lions-offensive, mobbing behavior that drives lions away-differed strikingly from the defensive retreat in response to humans.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…McComb et al (10) provide suggestive data that the age of the herd's matriarch affects their response to Maasai boys, with older matriarchs less likely to retreat from their voices than younger matriarchs. In another study, herds led by older matriarchs reacted more appropriately to threats from male lions than those led by younger, less experienced females (12). Typical responses to lions-offensive, mobbing behavior that drives lions away-differed strikingly from the defensive retreat in response to humans.…”
mentioning
confidence: 99%
“…Considering recent research on the impact of an elephant matriarch's experience and age on her herd's survivability (12,13), it is not surprising that individual life experience might also influence how elephants react to different potential threats. McComb et al (10) provide suggestive data that the age of the herd's matriarch affects their response to Maasai boys, with older matriarchs less likely to retreat from their voices than younger matriarchs.…”
mentioning
confidence: 99%
“…If differences in individual nutritional need or motivation of individuals maintains the distinction between leaders and followers in P. affinis, then these differences are not reflected in the relative size or percentage growth of leading larvae. It seems more likely that other mechanisms sustain this behavioural distinction, such as experience or familiarity with the environment [11,32].…”
Section: Discussionmentioning
confidence: 99%
“…Because followers in a shared system may choose whether or not to follow a certain individual, they can influence both collective movements and which individuals become leaders [10]. In some shared systems, individuals emerge as leaders because they are more informed, or have knowledge that is beneficial to the timing or direction of movement [11,12]. Such individual information can be crucial for a group when relocating or foraging, with informed individuals leading, or guiding, the uninformed [13].…”
Section: Introductionmentioning
confidence: 99%
“…McComb et al [5] showed that, in African elephants, female family groups hearing lion-roar playbacks were able to identify situations that represented the greatest danger and those with older matriarchs were particularly adept at recognizing the specific danger presented by male (as opposed to female) lions. Other research on elephant risk assessment has shown that African elephants retreat and alarm call in response to playbacks of threatening African bees [6].…”
Section: Introductionmentioning
confidence: 99%